Hubungan Kualitas Tidur dengan Gait Speed pada Mahasiswa Kedokteran - Nayoan, Oswaldo S.; Wungouw, Herlina I. S.; Polii, Hedison (Universitas Sam Ratulangi, 2026)
Abstract: Poor sleep quality can impair motor functions, including balance and neuromuscular coordination. Gait speed is widely recognized as an important indicator of both motor and cognitive function. Medical students frequently experience reduced sleep quality due to demanding academic workloads, yet no research has examined this relationship in Indonesia. This study aimed to determine the relationship between sleep quality and gait speed among medical students. This cross-sectional analytic study involved 80 first-year medical students (aged 16–20 years) of Faculty of Medicine Universitas Sam Ratulangi, Manado, with normal BMI. Sleep quality was measured using the Indonesian version of the Pittsburgh Sleep Quality Index (PSQI), while gait speed was assessed using a stopwatch over a 4-meter walkway. Data were analyzed using the Pearson correlation test. The results showed that 83.75% of participants had poor sleep quality (PSQI >5), and 12.50% demonstrated slow gait speed. There was a significant negative correlation between sleep quality and gait speed (r=-0.402; p=0.000). In conclusion, poor sleep quality is significantly associated with slower gait speed among medical students. Keywords: sleep quality; gait speed; medical students; motor function Abstrak: Kualitas tidur yang buruk dapat berdampak pada fungsi motorik, termasuk keseimbangan dan koordinasi neuromuskular. Gait speed dikenal sebagai indikator penting fungsi motorik dan kognitif. Mahasiswa kedokteran berisiko mengalami penurunan kualitas tidur akibat tuntutan akademik. Penelitian ini bertujuan menilai hubungan kualitas tidur dan gait speed pada mahasiswa kedokteran. Studi observasional analitik dengan desain potong lintang dilakukan pada 80 mahasiswa semester 1 Fakultas Kedokteran Universitas Sam Ratulangi Manado yang berusia 16–20 tahun dengan IMT normal. Kualitas tidur diukur menggunakan PSQI versi Indonesia, sementara gait speed diukur menggunakan stopwatch pada lintasan 4 meter. Analisis dilakukan menggunakan uji korelasi Pearson. Hasil penelitian mendapatkan sebanyak 83,75% responden memiliki kualitas tidur buruk (PSQI >5), dan 12,50% memiliki gait speed lambat. Terdapat korelasi negatif bermakna antara kualitas tidur dan gait speed (r=-0,402; p=0,000). Simpulan penelitian ini ialah kualitas tidur yang lebih buruk berhubungan bermakna dengan gait speed yang lebih lambat pada mahasiswa kedokteran. Kata kunci: kualitas tidur; gait speed; mahasiswa kedokteran; fungsi motorik